(untitled) (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2012.1.1.3908.55-73 The paper begins by showing concepts related to foresight and competitive intelligence processes and its respective methodologies, in order to illustrate how these methods can be applied in a business R&D center, through the implantation of an observatory of technological trends. The major aspects and variables considered in the construction of an observatory of trends are evidenced, indicating the role of foresight and competitive intelligence processes, and also emphasizing challenges and potential benefits that can be experienced by institutions in the moment of the implementation of observatories of trends in business R&D centers. The paper intends to indicate the possibility of using the concept of observatory of trends in business R&D centers in the technological management. It is possible to verify the importance of monitoring current actions through competitive intelligence techniques, and prospecting aspects related to future actions through foresight techniques, according to the specificities of each area.